Participatory management of city development: Polish experience and Ukraine’s prospects - Zhebchuk, Roman; Klapkiv, Yuriy (Uniwersytet Warszawski, 2017)
The sign of a mature democratic society is a constructive and mutually beneficial dialogue between the public administration and citizens. This connection should be constant at the national level for take in account the interests of diff erent social groups during development and implementation of public policies, regardless of its type. As we know, state functions primarily aimed to increase the welfare of its citizens. Th at is why public authorities must be open for suggestions and concerns of its citizens. But, even more urgent is the need of cooperation between authorities on citizens which felt at the local level – the level of cities. Because the public administration, at urban communities level, is in direct contact with the citizens in cases provision process of public services. As a result appear the need in eff ective mechanisms for such cooperation and establishment of appropriate regulatory background.
Keywords: Participatory management; city development